The Psychological Approach of Transpersonal Theory in Islamic Education - rahmi, Nafizatur; Putro, Khamim Zarkasih; SZ, Zaky Faddad (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2022)
This study aims to examine and describe the integration of the psychological approach of transpersonal theory in Islamic education. The method used in this research is the Library Research method using documentation as a data collection method and analyzing it with Content Analysis. The results show that transpersonal psychology integrates psychological concepts, theories, and methods with material and practice from individual subjects' spiritual disciplines. Its application in Islamic education, peace of mind, and faith is the basis for carrying out learning activities well. So, if it is associated with religion, humans will have a peaceful soul if they have strong, firm, and true faith and always remember Allah. So it can be concluded that the psychological approach of transpersonal theory directs the achievement of education by focusing on happiness and peace of mind, maximizing the potential of reason by contemplating and relying on God for the results or outputs of the educational process.